Comparative analysis of efficacy and quality of life between totally extraperitoneal sublay and intraperitoneal onlay mesh repair for ventral hernia - Miaofeng Wang; Wei Chen; Xiufeng Chu (Scientific Reports)
Abstract Ventral hernias pose a prevalent challenge in abdominal wall surgery, with ongoing advancements in repair techniques designed to enhance patient outcomes. This study evaluates the efficacy, safety, and socio-economic impact of Totally Extraperitoneal Sublay Repair (TES) versus Laparoscopic Intraperitoneal Onlay Mesh Repair (IPOM) for small to medium-sized ventral hernias, with a particular focus on postoperative quality of life and patient satisfaction. A retrospective cohort study was conducted, encompassing 125 patients who underwent ventral hernia repair between May 2018 and November 2023. The cohort included 55 patients treated with TES and 70 with Laparoscopic IPOM. Baseline characteristics, including age, gender, BMI, operative time, postoperative pain, hospitalization costs, and patient satisfaction score, were compared. Postoperative quality of life was evaluated through outpatient visits or telephone follow-ups. The propensity score matching (PSM) technique was applied in a 1:1 ratio to balance the significant differences in general characteristics between the two groups. Out of 125 patients, 70 cases were successfully matched using the PSM method, resulting in 35 cases in each group. The baseline characteristics of patients in groups were well-matched (P > 0.05). The TES group exhibited a significantly longer operative duration (P < 0.001); however, this group also experienced markedly reduced postoperative pain, decreased hospitalization costs, and diminished postoperative drainage (all P < 0.001). The length of hospital stay and the incidence of long-term complications were similar between the two groups. Follow-up evaluations at 3 and 6 months showed a significantly improved quality of life and higher patient satisfaction in the TES group. Both TES and IPOM demonstrate comparable safety and efficacy in the repair of ventral hernias. Although TES is associated with a longer operative duration, it provides significant advantages in postoperative quality of life, patient satisfaction, and cost-effectiveness, thereby supporting its broader clinical adoption.